The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1371/journal.pone.0224613
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the relationship between aryl-hydrocarbon receptor and β-catenin in human colon cancer cells

Abstract: β-Catenin is a multi-functional protein involved in cell adhesion and signal transduction and has a critical role in colorectal cancer development. β-Catenin positively regulates the aryl-hydrocarbon receptor (AhR) mediated signal by both induction of AhR expression and enhancement of AhR-dependent gene induction. Conversely, it was reported that AhR negatively regulates the β-catenin signal via ubiquitination and subsequent degradation in a ligand dependent manner. However, there have been conflicting data am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Shiizaki et al showed that AhR activation induces β-catenin ubiquitination and subsequent proteosomal degradation. Thus AhR −/− mice spontaneously developed cecal tumors as the result of aberrant β-catenin accumulation [52] [53]. Similarly, treatment with TCDD (0.1-100 nM) diminishes colony formation and proliferation of human colorectal cancer cells [54].…”
Section: Ahr As a Tumor Suppressormentioning
confidence: 99%
“…Shiizaki et al showed that AhR activation induces β-catenin ubiquitination and subsequent proteosomal degradation. Thus AhR −/− mice spontaneously developed cecal tumors as the result of aberrant β-catenin accumulation [52] [53]. Similarly, treatment with TCDD (0.1-100 nM) diminishes colony formation and proliferation of human colorectal cancer cells [54].…”
Section: Ahr As a Tumor Suppressormentioning
confidence: 99%
“…Shiizaki et al showed that AhR activation induces β-catenin ubiquitination and subsequent proteosomal degradation. Thus, AhR −/− mice spontaneously developed cecal tumors as the result of aberrant β-catenin accumulation [ 52 , 53 ]. Similarly, treatment with TCDD (0.1–100 nM) diminishes colony formation and proliferation of human colorectal cancer cells [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…While it has been reported that the Wnt/β-catenin signaling pathway serves an important role in the progression of colon cancer (19,20), the mechanism underlying its hyperactivation is not fully understood. in the current study, it was demonstrated that the increased expression levels of β-catenin and c-myc proteins, together with the nuclear accumulation of β-catenin protein, could be induced by G3BP1 overexpression, with no notable change in the expression levels of Frz, Dsh, TCF, Axin and APC.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms via which G3BP1 facilitates colon cancer progression and the clinical values of G3BP1 require further investigation. Previous studies have revealed that aberration of the Wnt/β-catenin signaling pathway significantly contributes to the malignant transformation of colon cancer (19,20). inhibition of Wnt/β-catenin is suggested to be an anti-tumor mechanism in colon cancer (21).…”
Section: Overexpression Of G3bp1 Facilitates the Progression Of Colonmentioning
confidence: 98%
See 1 more Smart Citation